Hand-Held Spectrophotometer Design for Textile Fabrics - YILDIZ, KAZIM; BÖCEKÇİ, VEYSEL GÖKHAN (AMER INST PHYSICS, 2017)
In this study, a hand-held spectrophotometer was designed by taking advantage of the developments in modern optoelectronic technology. Spectrophotometer devices are used to determine the color information from the optic properties of the materials. As an alternative to a desktop spectrophotometer device we have implemented, it is the first prototype, low cost and portable. The prototype model designed for the textile industry can detect the color tone of any fabric. The prototype model consists of optic sensor, processor, display floors. According to the color applied on the optic sensor, it produces special frequency information on its output at that color value. In Arduino type processor, the frequency information is evaluated by the program we have written and the color tone information between 0-255 ton is decided and displayed on the screen.
Keywords: DEFECT DETECTION